2017
DOI: 10.1016/j.whi.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Breast Cancer Worry in a Hispanic and Predominantly Immigrant Mammography Screening Population

Abstract: Objective Worry about developing breast cancer (BC worry) has been associated with participation in screening and genetic testing and with follow-up of abnormal screening results. Little is known about the scope and predictors of BC worry in Hispanic and immigrant populations. Methods We collected in-person interview data from 250 self-identified Hispanic women recruited from an urban mammography facility (average age 50.4 years; 82% foreign-born). Women reported whether they worried about developing breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…These findings may not reflect women’s experiences at smaller community clinics or in rural areas. In addition, we previously reported a high level of breast cancer worry in the catchment community of the current study, which included regularly screened women with pro‐screening attitudes. Thus, the current study results, particularly in terms of interest in following a more intensive breast cancer screening, may not describe the full breadth of women’s perspectives, including those of women with a more limited screening history.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These findings may not reflect women’s experiences at smaller community clinics or in rural areas. In addition, we previously reported a high level of breast cancer worry in the catchment community of the current study, which included regularly screened women with pro‐screening attitudes. Thus, the current study results, particularly in terms of interest in following a more intensive breast cancer screening, may not describe the full breadth of women’s perspectives, including those of women with a more limited screening history.…”
Section: Discussionmentioning
confidence: 97%
“…Participants were drawn from a sample of women who were enrolled into an ongoing observational study from a large screening mammography clinic in New York City. Of this study sample, 41 women met the eligibility criteria of self‐identifying as Hispanic and having a history of dense breasts since the enactment of NYS notification legislation, defined according to the BDN legislation (BI‐RADS density categories c and d) . Participant characteristics and risk factors were assessed at the time of enrollment (2012‐2014), which occurred on average 2.5 years prior to the qualitative interviews in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…We used data from the first two waves of the New York Mammographic Density Study, an ongoing study of breast cancer screening and prevention in women, recruited during screening mammography visits at a community clinic in New York City (24,25); women presenting for diagnostic mammograms attended a different mammography site. We followed the same standard protocol for recruitment and data collection in both study waves, yielding a study sample representative of the racial/ethnic and sociodemographic distribution of the community, although our sample had a higher proportion of foreign-born women than in the community due to the older age range in our sample (26).…”
Section: Methodsmentioning
confidence: 99%
“…Two SRs (including seven studies [ 16 ] and seven studies [ 19 ] each) and three cross-sectional studies found a negative association between age and psychosocial morbidity in screening for breast [ 22 , 23 ], pancreatic [ 16 ], cervical [ 29 ], and colorectal [ 19 ] cancers.…”
Section: Resultsmentioning
confidence: 99%